‘Fend for yourself’: Nurses’ experiences transitioning to Family Care Team practice settings in Newfoundland and Labrador - Robin Devey-Burry; Julia Lukewich; Dana Ryan; Myuri Sivanthan; Maria Mathews; Marie-Eve Poitras; Cheryl Etchegary; Shabnam Asghari; Margot Antle (PLoS ONE, 2026)
Background Family Care Teams were introduced in Newfoundland and Labrador (NL) as a strategy to strengthen primary care through team-based models that optimize interprofessional collaboration. Nurses, including nurse practitioners (NPs), registered nurses (RNs), and licensed practical nurses (LPNs), play critical roles in these models; however, little is known about nurses’ transition to these settings or the supports shaping their integration and effectiveness. To address this gap, we explored nurses’ experiences transitioning into Family Care Teams, including supports for integration and the barriers and facilitators influencing this process. Methods As part of a qualitative descriptive study, we conducted semi-structured interviews with 25 nurses (6 NPs, 13 RNs, 6 LPNs) employed in Family Care Teams across five NL health zones. During the interviews, nurses described their experiences working in Family Care Teams, available practice supports, current roles, and barriers and facilitators to maximizing scope of practice. Interviews were transcribed and analyzed using qualitative content analysis and constant comparison. Results Participants described their transition to Family Care Teams in two stages: 1) orientation and 2) supportive learning relationships. Orientation was highly variable, ranging in length and structure. Learning in this area was often self-directed, technology-focused, and asynchronous, with limited emphasis on clinical preparation or role expectations. Mentorship and shadowing opportunities were inconsistently available, with many nurses lacking access to experienced role models within the newly established teams. These gaps contributed to role ambiguity, underutilization of nursing scope of practice, and prolonged adjustment periods. Conclusions Our findings reveal gaps in orientation and mentorship during nurses’ transition into Family Care Teams in NL. A common yet adaptable transition framework, expanded student placements, and structured mentorship are critical to optimizing nursing roles in team-based care. Strengthening practice supports and clarifying nursing contributions can improve access and care quality while informing broader initiatives to support nurses’ transition into primary care.